2009
DOI: 10.2214/ajr.08.1869
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Pediatric Urinary Tract Infection: A 9-Year Local Experience

Abstract: For children younger than 2 years with UTI in the absence of underlying major congenital urinary tract abnormalities, we recommend that DMSA scintigraphy may be withheld if findings on both ultrasound and MCU examinations are normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In recurrent UTI children may develop long-term complications like renal parenchymal scarring, hypertension, chronic impaired renal function and end stage renal failure, if not treated adequately. But UTI in children recovered with an excellent prognosis if it is diagnosed timely and treated adequately (7,9).So that timely diagnosis of underlying abnormalities or pathologies of urinary tract and adequate treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recurrent UTI children may develop long-term complications like renal parenchymal scarring, hypertension, chronic impaired renal function and end stage renal failure, if not treated adequately. But UTI in children recovered with an excellent prognosis if it is diagnosed timely and treated adequately (7,9).So that timely diagnosis of underlying abnormalities or pathologies of urinary tract and adequate treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvicalyceal dilatation was detected more by US than DMSA scan. Study reported that ultrasound is more reliable for determining mild renal obstruction, as well as it is a simple and non-invasive means (7,8). The mild dilatation in collecting system could not be evident in DMSA, which is a cortical imaging agent, and its minimum excretion (only 25%) is through the collecting system (6,13).…”
Section: Discussionmentioning
confidence: 99%
“…Acute pyelonephritis and reflux diagnosed by several imaging methods; ultrasonography, IVP, VCUG , CT , Doppler , DMSC scintigraphy and MRU. Danger of exposure to radiation is important in patients.Renal ultrasonography and renal scanning at the time of the acute illness are of limited value, because they do not provide information that modifies management (12)(13)(14)(15)(16)(17)(18) sensitive enough to detect the presence of hydronephrosis, hydroureter, acute pyelonephritis, or renal scarring (11) VUR which affects approximately 30 to 40 percent of young children cannot be consistently detected by US has been an important consideration in ultrasonography.…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%
“…Both type of nephropathy are best demonstrated on IVP or US and CT as classically lobar, with normal lobes with normal calyces interposed between diseased lobes. (11)(12)(13)(14)(15)(16)(17) CT is more sensitive than Ultrasound in demonstrating subtle changes in the renal parenchyma associated with uncomplicated pyelonephritis. CT is normal in some patients with mild uncomplicated pyelonephritis.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study of children under 10 years of age who presented with a culture-proven UTI and were evaluated with an early DMSA scan, VCUG, and renal ultrasound, Luk et al [33] found that the negative predictive value of ultrasound and VCUG was high in predicting the absence of renal scarring, especially in children less than 2 years old (2.3%), but in the 6-to 10-year age group the negative predictive value was only 10%. Although 583 children were included in this study, most patients were between 0 and 2 years of age; only 16 were in the 6-to 10-year age group.…”
Section: Is Vesicoureteral Reflux a Predictor Of Renal Scarring?mentioning
confidence: 99%